THE GENUS SAISSETIA DEPLANCHE IN CHILE (HOMOPTERA: COCCIDAE) (Acta Entomológica Chilena, 2022)
A survey of the black scales belonging to lite genus Saisselia was conducted between the hf and Hl/iRegions in Chile. Notwithstanding the wide array of female scale covering, a characler related to the hostplant. only two species, namely S. cofjeae (Walker) and 5. oleae (Olivier), were determined.
Keywords: Saissetta, Chile, host plants, distribution